Equity and efficiency of Minnesota educational expenditures with a focus on English learners, 2003-2011: A retrospective look in a time of accountability - Nicola A. Alexander; Sung Tae Jang (Arizona State University, 2017)
Policymakers and practitioners often must balance distributing resources equitably and efficiently while being accountable for high student achievement. This paper focuses on these concepts as they relate to English learners and examines equity and efficiency in Minnesota's educational funding from 2003 through 2011, the years spanning implementation of the No Child Left Behind Act and Minnesota's waiver from its regulations. Equity refers to the distribution of resources in the achievement of established goals (Alexander, 2012); efficiency entails the attainment of those goals using fewer resources (Rolle, 2004). We measure equity by looking at three standard distribution measures: (1) McCloone Index; (2) Verstegen Index; and (3) Coefficient of Variation (Odden Picus, 2008). We operationalize efficiency using data envelope analysis, thus getting at aspects of technical efficiency. We found that distribution of expenditures are increasingly uneven in the nine-year period examined. This inequality was largely driven by low-spending districts falling farther behind the median. Moreover, despite specific guidelines in its school finance formula that awarded additional resources for English learner populations, districts with higher portions of English learners have lower total and instructional expenditures per pupil, not higher. If more dollars are not available for EL programming, then doing more with less becomes paramount. Nevertheless, the efficiency of resource use was relatively constant over the years examined with efficiency in the use of education resources similar for English learners as it was for the population overall.